Implementation of Legal Aid for the Poor as a Form of Practicing Pancasila Values - Choerul Amin (Universitas Negeri Semarang, 2021)
Provision of Legal Aid is one of the ways the state can achieve access to law and justice for poor people in accordance with what has been mandated by the constitution. The principle of equality before the law in the Criminal Procedure Code (KUHAP) and Article 27 paragraph (1) of the 1945 Constitution tries to be realized by the state with this legal assistance so that the poor will experience justice in law enforcement in Indonesia. Justice is the right of all Indonesian people. Justice can be obtained by all people, this is contained in the Pancasila Values ​​especially in the 5th (five) precepts which read